2006
DOI: 10.1002/mc.20258
|View full text |Cite
|
Sign up to set email alerts
|

Dual action on promoter demethylation and chromatin by an isothiocyanate restored GSTP1 silenced in prostate cancer

Abstract: Prostate carcinoma is characterized by the silencing of pi-class glutathione S-transferase gene (GSTP1), which encodes a detoxifying enzyme. The silencing of GSTP1, due to aberrant methylation at the CpG island in the promoter/5'-UTR, occurs in the vast majority of prostate tumors and precancerous lesions. It is a pathologic marker and probably an underlying cause of oxidative damage and inflammation at tumor initiation. Inhibition of the aberrant promoter methylation could therefore be an effective mean to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(92 citation statements)
references
References 33 publications
5
85
0
1
Order By: Relevance
“…In these cells, PEITC exposure induced demethylation of the CpG island of the GSTP1 promoter, and ultimately reactivated GSTP1 expression 64. In this study, PEITC was shown to decrease the activity of HDAC1 and HDAC2, and decrease the expression of the HDAC1.…”
Section: Peitc and Epigenetic Regulation: An Emerging Fieldmentioning
confidence: 50%
“…In these cells, PEITC exposure induced demethylation of the CpG island of the GSTP1 promoter, and ultimately reactivated GSTP1 expression 64. In this study, PEITC was shown to decrease the activity of HDAC1 and HDAC2, and decrease the expression of the HDAC1.…”
Section: Peitc and Epigenetic Regulation: An Emerging Fieldmentioning
confidence: 50%
“…With Pyrosequencing, as many as 10 CpG sites can be studied in the same assay (14,15). CpG sites are thought to be involved in cancer development and have been extensively studied (13,(16)(17)(18)(19)(20)(21)(22), and it has been shown that exposure of carcinogens affects the DNA methylation patterns (23)(24)(25). Furthermore, the significance of the methylation pattern is also shown by the SNRPN gene which is a candidate for diagnostic tests in Prader-Willi syndrome and Angelman syndrome (26).…”
Section: Discussionmentioning
confidence: 99%
“…Lysates from cell cultures or tissues were prepared in the presence of HDAC inhibitor sodium butyrate at 5 mM final concentration as previously described. Histones were isolated using an acid extraction procedure (18,19). The procedures for quantitative Western blotting were performed as previously described (18), with site-specific antibodies against acetylated lysines 4, 9, 14, 23, or 27 of histone H3 (Millipore).…”
Section: Methodsmentioning
confidence: 99%
“…HDAC activity of classes I, II, and Sirt1 was detected with a previously described procedure using a HDAC assay kit (Biomol International) (18). The assay uses a synthetic acetylated lysine side chain as a substrate to react with the deacetylase samples in a 96-well microplate.…”
Section: Methodsmentioning
confidence: 99%